DeMille-the-Businessman and the Mini-Me Mirroring of Samson in Young Saul within Samson and Delilah - Kozlovic, Anton Karl (2021)
Legendary producer-director Cecil B. DeMille was a master of the American biblical epic and a devout Hollywood businessman whose films inspired numerous extra-cinematic products plus screen characters designed to match market demographics whilst promoting public piety. For example, his main biblical protagonists within his family-friendly Samson and Delilah were crafted to appeal to adult audiences, but it is argued that DeMille also meticulously crafted young Saul (Russell Tamblyn) as a mini-me mirror of Samson (Victor Mature) to directly appeal to his youthful audiences, thereby assisting box office sales and helping shape US Christian culture. DeMille’s filmmaker status, businessman background, and ten Samson-Saul parallels are explicated here, guided methodologically by humanist film criticism plus a selective review of the critical literature. This original investigation reveals that DeMille was a far more insightful, creative, and business-savvy filmmaker than previously acknowledged. Further research into DeMille studies, biblical epics, and the emerging interdisciplinary field of religion and film is recommended.
Keywords: Cecil B. DeMille; Hollywood; Russell Tamblyn; Samson; Samson and Delilah (1949); Saul; Victor Mature; biblical epic; Business; religion and film